2022
DOI: 10.3390/molecules27217469
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Research on Bioactivity, Toxicity, Metabolism, and Pharmacokinetics of Usnic Acid In Vitro and In Vivo

Abstract: Lichens are among the most widely distributed plants on earth and have the longest growth cycle. Usnic acid is an abundant characteristic secondary metabolite of lichens and the earliest lichen compound used commercially. It has diverse pharmacological activities, such as anti-inflammatory, antibacterial, antiviral, anticancer, antioxidant, and photoprotective effects, and promotes wound healing. It is widely used in dietary supplements, daily chemical products (fodder, dyes, food, perfumery, and cosmetics), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 115 publications
1
16
0
Order By: Relevance
“…A significant synergistic effect of the COL/UA combination on all tested isolates was demonstrated via checkerboard assays and time-kill curve tests. Due to the dose-dependent toxic side effects of UA, its medical application is limited . Our study yielded effective results with a reduced dosage of UA, which reflects the potential use of this combination in future systematic research.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…A significant synergistic effect of the COL/UA combination on all tested isolates was demonstrated via checkerboard assays and time-kill curve tests. Due to the dose-dependent toxic side effects of UA, its medical application is limited . Our study yielded effective results with a reduced dosage of UA, which reflects the potential use of this combination in future systematic research.…”
Section: Discussionmentioning
confidence: 53%
“…25 Hence, there is a growing interest in synthesizing UA derivatives or developing combination therapies with conventional antibiotics. 26 Bernardetta Segatore et al reported the synergistic effect of UA in combination with gentamicin against MRSA. 27 In addition, the combined action of UA and norfloxacin in disrupting cell membrane stability and metabolic homeostasis has been shown to synergistically combat MRSA.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Usnic acid (UA), also known as lichen acid, widely exists in lichen plants and is a natural furan antibiotic, which has been partially used in cosmetics, health products, and bacteriostatic agents [ 26 , 27 ]. Moreover, UA has good antibacterial effect and biological activity in vitro, and can effectively inhibit the growth of E. coli , S. thermophilus , S. pyogenes, and other bacteria [ 28 ].…”
Section: Introductionmentioning
confidence: 99%